IN SEARCH OF ISLAMIC DEFINITION OF WORLDVIEW: ELEMENTS, AND ITS CHARACTERS - Muhammad Taqiyuddin (IAIN Kendari, 2020)
The discourse about worldview rapidly developed in harmony with the philosophy of science itself. The reason is that globalization has 'challenged' various nations and countries to develop science and technology; some even seem to negate others. At this stage, civilization experiences a 'clash'; namely at the level of natural outlook (clash of worldview). That is, differences in culture, nation, race and religion also confirm the definitive difference between the worldview of Islam and non-Islam. Furthermore, the true concept of the Islamic worldview can be defined based on the elements and characteristics that are fundamental to Islam philosophically. This literature research model seeks to offer efforts to define the Islamic worldview historically; that is, from the very beginning of the emergence of this concept until the 'maturity' of the concept of the Islamic worldview in the hands of Muslim scholars; and possible future developments. Data analysis is carried out critically and comparatively. This study concludes that the meaning of worldview can be traced based on its origin, which is used in the secular Western era. Then, Christians also adapted it as part of the explanation of religious philosophy, especially systematic theology. But essentially, some elements and worldview characters can be filled with the nature and values of Islam; so that we can also define the meaning of the Islamic worldview along with its essential aspects.